2015
DOI: 10.1158/1541-7786.mcr-15-0089
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically Increasing Mdm2 Inhibits DNA Repair and Cooperates with Genotoxic Agents to Kill p53-Inactivated Ovarian Cancer Cells

Abstract: The Mdm2 oncogene is a negative regulator of the p53 tumor suppressor and recently identified inhibitor of DNA break repair. Nutlin-3 is a small molecule inhibitor of Mdm2/p53 interaction that can induce apoptosis in cancer cells through activation of p53. While this is promising therapy for those cancers with wild-type p53, half of all human cancers have inactivated p53. Here, we reveal a previously unappreciated effect of Nutlin is inhibition of DNA break repair, stemming from its ability to increase Mdm2 pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Mdm2 protein levels were increased in p53 -null sarcoma cells treated with Nutlin-3 (Fig. 7C), as we and others previously reported in other cell types (11,33,34). Notably, sarcoma cells treated with 30μM Nutlin-3 showed no change in cell number in G 2 /M over 48 hours relative to control; however, there was a significant increase of cells in G 1 of the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Mdm2 protein levels were increased in p53 -null sarcoma cells treated with Nutlin-3 (Fig. 7C), as we and others previously reported in other cell types (11,33,34). Notably, sarcoma cells treated with 30μM Nutlin-3 showed no change in cell number in G 2 /M over 48 hours relative to control; however, there was a significant increase of cells in G 1 of the cell cycle (Fig.…”
Section: Resultssupporting
confidence: 88%
“…However, recently, new approaches to capitalize on the genome instability of cancer cells for treatment are being tested. For example, pharmacologically increasing Mdm2 levels with Nutlin in ovarian carcinoma cells that lack functional p53 causes a delay in DNA break repair that results in increased sensitivity to DNA-damage agents, such as cisplatin and etoposide (Carrillo et al 2015b). Topoisomerase II inhibitors were shown to cooperate with Nutlin in pancreatic cancer cells that lacked functional p53 (Conradt…”
Section: Discussionmentioning
confidence: 99%
“…While our studies do not demonstrate a direct interaction of chromatin-associated Mdm2 with the MRN complex, increases in Mdm2 associated chromatin following Nutlin-3a or combination Nutlin-3a/carboplatin are consistent with studies of Eischen and colleagues. They demonstrated that Nutlin-3a–induced increased levels of Mdm2 directly inhibit DNA damage response signaling and delayed DNA break repair in p53 -null MEFs and in ovarian cancer cell lines that lacked p53 or that contained mutant p53 (48). Combination treatment and dosing strategies that reduce the amount of required chemotherapeutics are important clinically to decrease normal tissue toxicity as well as prevent the emergence of secondary malignancies caused by therapies that damage DNA.…”
Section: Discussionmentioning
confidence: 99%